EFFICACY OF FREE AUTOVENOUS TRANSPLANT IN FEMORAL-POPLITEAL BYPASS BELOW THE JOINT SPACE OF THE KNEE - B. S. Sykovatykh; L. N. Belikov; M. B. Sykovatykh; D. V. Sidorov; M. A. Inarkhov; E. B. Inikhodova (Вестник хирургии имени И.И. Грекова, 2016)
The article presents an analysis of complex examination and treatment of 60 patients with critical ischemia of the lower extremities due to atherosclerotic lesions of femoral-poplitealtibia segment. Typical traditional autovenous bypass of reverse big saphena was performed for the first (control) group of patients. The operation, which used an original technology by free autovenous transplant with collapsed valves without vein reverse, was completed for the second (experimental) group of patients. An application of original treatment technology allowed an increase of blood flow volume in the extremity in 1,5 times, an arterial blood flow - in 1,6 times, rate of microcirculation - in 1,3 times. An early postoperative complications were decreased on 23,4%, the late shunt thrombosis - on 40%. Long-term shunt passability was improved in 2,6 times and physical component of health - on 10,6%, psychological - on 4,3%. The shunt functioned in 36,7% of the first group and in 83,3% patients of the second group after two years since operation. The extremity was saved in 60% of the first group and 90% patients of the second group.